A simple, cost-effective, and sustainable method for extraction and quantification of chebulagic acid from Terminalia bellirica (Gaertn.) Roxb. using RP-HPLC: A comparative study - Nisha Nerlekar; Aditya Magdum; Vinod Nandre; Mansingraj Nimbalkar; Padma Dandge (Green Analytical Chemistry)
Chebulagic acid (CA), a hydrolysable tannin found in Terminalia bellirica (T. bellirica) (Gaertn.) Roxb., has gained prominence as a significant component in Ayurvedic medicine. This study optimized methods for determining CA in T. bellirica, focusing on fruit samples and prioritizing simplicity, cost-effectiveness, less time duration, and sustainability. We evaluated various extraction techniques, including continuous shaking, microwave assisted extraction, and Soxhlet extraction using green solvents. Quantification of CA was conducted using Reverse Phase High-Performance Liquid Chromatography (RP-HPLC), with confirmation achieved via UV–Visible (UV–Vis) spectroscopy, Thin Layer Chromatography (TLC), and Liquid Chromatography-High Resolution Mass Spectrometry (LC-HRMS). Results indicated that Soxhlet and microwave significant extraction methods, particularly with ethanol as the green solvent. Soxhlet extraction yielded 49,607.73±18.82 μg/mL for fresh fruit and 42,952.53±19.09 μg/mL for dry fruit, while microwave extraction resulted in 43,627.56±113.48 μg/mL for fresh fruit and 40,466.33±130.90 μg/mL for dry fruit respectively. These findings conclude that ethanol as a green solvent in Soxhlet or microwave assisted extraction emerge as most efficient, straightforward, and effective approach for detecting and screening CA in T. bellirica samples.